A method for detecting single mRNA molecules in Arabidopsis thaliana. Issue 1 (December 2016) - Duncan, Susan; Olsson, Tjelvar; Hartley, Matthew; Dean, Caroline; Rosa, Stefanie
Abstract Background Despite advances in other model organisms, there are currently no techniques to explore cell-to-cell variation and sub-cellular localization of RNA molecules at the single-cell level in plants. Results Here we describe a method for imaging individual mRNA molecules inArabidopsis thaliana root cells using multiple singly labeled oligonucleotide probes. We demonstrate detection of both mRNA and nascent transcripts of the housekeeping geneProtein Phosphatase 2A . Our image analysis pipeline also enables quantification of mRNAs that reveals the frequency distribution of transcripts per cell underlying the population mean. Conclusion This method allows single molecule RNA in situ to be exploited as a powerful tool for studying gene regulation in plants.